How do you solve #6( 6x + 9) - 3= 9x + 6#?

2 Answers

Answer:

Distribute across the parenthesis and solve for #x#

#x = -5/3#

Explanation:

#6(6x +9) -3 = 9x+6#

#36 x + 54 -3 =9x+6" " # so now combine like terms

# 36x +51 = 9x + 6" "# subtract #9x and 51# from both sides

# 36x - 9x + 51 -51 = 9x -9x + 6 - 51" " # gives

# 27x = -45" "# dividing both sides by 27 gives

# (27x)/27 = (-45)/27# gives

#x = -5/3#

# x = - 1 2/3 #

Jul 21, 2017

#6(6x+9)-3=9x+6#
#36x+54-3=9x+6#
#36x-9x=-54+3+6#
#27x=-54+9#
#27x=-45#
#x=frac(-45) 27#
Both are divisible by 9
#x=frac(-5) 3#